1998
DOI: 10.1038/sj.bmt.1701266
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine treatment for chronic replicative hepatitis B virus infection after allogeneic bone marrow transplantation

Abstract: The risk of severe hepatic damage in patients with chronic hepatitis B virus (HBV) infection is well known; more effective treatments for this infection are needed. Lamivudine is being studied in immunocompetent and immunosuppressed HBV infected patients. We report a patient suffering from chronic replicative HBV infection after allogeneic BMT, who responded to lamivudine therapy. A 24-year-old woman with CML received an allogeneic BMT from her HLA-identical sister in June 1992. Before transplant, her HBV stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 9 publications
1
34
0
2
Order By: Relevance
“…In the present study, only one of three patients with reverse seroconversion had biochemical signs of liver damage. In contrast, the vast majority of reported patients with reverse seroconversion after allo-HSCT were identified only because they developed clinical hepatitis (Table 2); (iii) changes in immunosuppressive therapy strategies, for example, the use of mycophenolate mofetil as given to the majority of our patients, could influence risk of HBV reactivation; (iv) HBV reactivation has been reported as late as 2 years after complete clearance of anti-HBs, anti-HBc and anti-HBe 15 or 51 months after HSCT and 40 months after cessation of immunosuppressive therapy, 20 suggesting that HBV reactivation was due not only to immunosuppression but also to reconstitution with donor-derived naive immunity against HBV. Therefore, the risk of reactivation of latent HBV could increase in long-term allo-HSCT survivors and would be underestimated in studies with a short follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, only one of three patients with reverse seroconversion had biochemical signs of liver damage. In contrast, the vast majority of reported patients with reverse seroconversion after allo-HSCT were identified only because they developed clinical hepatitis (Table 2); (iii) changes in immunosuppressive therapy strategies, for example, the use of mycophenolate mofetil as given to the majority of our patients, could influence risk of HBV reactivation; (iv) HBV reactivation has been reported as late as 2 years after complete clearance of anti-HBs, anti-HBc and anti-HBe 15 or 51 months after HSCT and 40 months after cessation of immunosuppressive therapy, 20 suggesting that HBV reactivation was due not only to immunosuppression but also to reconstitution with donor-derived naive immunity against HBV. Therefore, the risk of reactivation of latent HBV could increase in long-term allo-HSCT survivors and would be underestimated in studies with a short follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…It has also recently been reported that this drug is also useful for the treatment of viral hepatitis after cytotoxic therapy. 8,9 In the present patient lamivudine appeared to work to not only avoid HBV exacerbation during transplantation, but also to treat reactivation of HBV later.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Several studies have shown the effectiveness of lamivudine for inhibition of HBV reactivation and for clinical and pathological improvement in hepatic dysfunction even in patients with hematological diseases after stem cell transplantation. 7,8 Here, we report a successful allogeneic BMT from an HBV-positive sibling donor (HBV carrier) into a patient with severe aplastic anemia complicated by chronic hepatitis B, using lamivudine. …”
mentioning
confidence: 99%